شعر ادريس بن اليمان اليابسي "ت. 470 هـ.": دراسة أسلوبية - عودة، خولة عبدالحميد; حميد، نضال مهدي (جامعة بغداد - كلية الآداب, 2023)
تسعى هذه الدراسة إلى إبراز السمات الأسلوبية لشاعر أندلسي هو إدريس بن اليمان، واجتلاء المظاهر الجمالية لنصوصه الشعرية، من خلال ثلاثة مباحث: تضمن المبحث الأول البنية الإيقاعية بوساطة الأساليب الإيقاعية التي استعملها في شعره كالإيقاع الخارجي والداخلي، وأبرزت مقدرته على اختيار اللغة المناسبة للبحر والقافية، فضلا عن التكرار والتوازي لتعزيز الإيقاع. وخصص المبحث الثاني للبنية التركيبية من استفهام، ونداء، والتركيب الفعلي مما أكسب شعره البعد الجمالي والفني. أما المبحث الثالث فتضمن البنية الدلالية وإبراز دور الصورة الفنية وإيصالها إلى الملتقى بأبهى صورة، وقد استعان إدريس بالتشبيه، والاستعارة، والكناية، لتوضيح معانيه وإضفاء الصفة الجمالية لنصوصه الشعرية. وأخيرا اختتم البحث بخاتمة بما توصل إليه، ثم ثبت المصادر والمراجع. This study tends to highlight the stylistic features of an Andalusian poet, Idris bin Al-Yaman, and to expose the aesthetic aspects of his poetic writings, through three topics: The first topic includes rhythmic via rhythmic methods used in his poetry such as external and internal rhythm structure. The appropriate language of poetic line and rhyme, as well as repetition and parallelism, are used to enhance the rhythm in his poetry. The second topic has been devoted to the synthetic structure of a question, an appeal, and the actual composition, which gave his poetry an aesthetic and artistic dimension. As for the third topic, it included the semantic structure and highlighting the role of the artistic image and its delivery to the audience in the best way. Idris used analogy, and metaphor to clarify his meanings and to give aesthetic character to his poetic texts. Finally, the research has ended with a conclusion, and then the sources and references cited.
Keywords: الأدب العربي -- السمات الأسلوبية -- الصورة الفنية -- الأغراض الشعرية -- النصوص الشعرية